AB0687 Non-Invasive Assessment of Muscle Quality by MRI as a Potential Marker of Disease Modification in Bimagrumab-Treated SIBM Patients. (9th June 2015) - Laurent, D.; Tseng, B.; Greenberg, S.; Houston, P.; Papanicolaou, D.; Roubenoff, R.
Abstract : Background: Bimagrumab is a monoclonal antibody that inhibits ligand binding to the activin receptor IIA/B thereby stimulating muscle growth. In a proof of concept study, bimagrumab increased thigh muscle volume (TMV) by 6.5% (p=0.024) and decreased intramuscular adipose tissue (IMAT) by 3% (p=n.s.) after 8 weeks of treatment. Objectives: Using qualitative muscle MRI to characterize disease severity and modification in sporadic inclusion body myositis (sIBM) patients treated with bimagrumab. Methods: 14 patients were randomized to single IV dose (30 mg/kg) of bimagrumab (n=11) or placebo (n=3). Disease severity was assessed by visual scoring of PD images. TMV, IMAT, subcutaneous (SC) adipose tissue volume, and individual muscle volume (IMV) were determined from proton-density (PD) MR images using semi-automated segmentation approaches. In addition, the relative fat fraction (%FF) and apparent coefficient of diffusion (ADC) were measured from three-point Dixon and diffusion-weighted images, respectively. Results: After 8 weeks of treatment, mean score for disease activity (21.5±0.6) remained unchanged. Although insignificant, decrease in %FF (−7% vs baseline) was seen at Week-8 in 4 patients while SC and IMAT volumes were slightly reduced. At baseline, fat-infiltrated muscles had lower ADC values than previously reported (1.46±0.11 vs 1.62±0.14 x10 -3 mm 2 /sec) and a trend towards normal values was observed after treatment. At baseline, IMAT content was greater in anterior than in posterior thigh muscles (49% vs 23%, p<0.01). Individual muscle volumes (IMV) increased more in the posterior (+8%) than in anterior thigh compartment (+4%, p<0.01). At Week-16, further decrease in IMAT in all muscles (-7% vs baseline, p<0.05) correlated well with the change from baseline in IMV at Week-8 (r=0.57, p<0.05). Conclusions: MRI may be used in a comprehensive non-invasive way to demonstrate potential of bimagrumab as a disease-modifying therapy which may potentially lead to restoration of normal muscle quality and composition. References: Amato AA et al. Neurology. 2014;83(24):2239-46. Qi J et al. J Magn Reson Imaging. 2008;27(1):212-7. Acknowledgements: Study Supported By: Novartis Pharma AG Disclosure of Interest: D. Laurent Shareholder of: Novartis, Employee of: Novartis Institutes for Biomedical Research, Basel, Switzerland, B. Tseng Employee of: Novartis Institutes for Biomedical Research, Cambridge, USA, S. Greenberg Grant/research support from: Novartis Pharma AG, P. Houston Employee of: Novartis Pharma AG, Basel, Switzerland, D. Papanicolaou Employee of: Novartis Pharmaceuticals Corporation, East Hanover, USA, R. Roubenoff Employee of: Novartis Institutes for Biomedical Research, Basel, Switzerland.